Post-marathon Decline in Right Ventricular Radial Motion Component Among Amateur Sportsmen - Lewicka-Potocka, Zuzanna; Kaleta-Duss, Anna Maria; Lewicka, Ewa; Kubik, Marcin; Faran, Anna; Szymeczko, Paweł; Gała̧ska, Rafał; Raczak, Grzegorz; Da̧browska-Kugacka, Alicja (Frontiers in Physiology, 2022)
Moderate physical activity has a positive impact on health, although extreme forms of sport such as marathon running may trigger exercise-induced cardiac fatigue. The explicit distinction between the right ventricular (RV) physiologic response to training and maladaptive remodelling has not yet been determined. In this study, we aimed to analyse the impact of running a marathon on RV mechanics in amateur athletes using three-dimensional (3D) echocardiography (ECHO) and the ReVISION method (RV separate wall motion quantification). A group of 34 males with a mean age of 40 ± 8 years who successfully finished a marathon underwent ECHO three times—2 weeks before the marathon (stage I), at the marathon finish line (stage II) and 2 weeks after the marathon (stage III). The ECHO findings were then correlated with concentrations of biomarkers related to myocardial injury and overload, also obtained at the three stages. Upon finishing the marathon, the amateur athletes were found to have a significant (p < 0.05) increase in end-diastolic (with median of 51.4 versus 57.0 ml/m2) and end–systolic (with median of 24.9 versus 31.5 ml/m2) RV volumes indexed to body surface area, reduced RV ejection fraction (RVEF) (with median of 51.0 versus 46.0%) and a decrease in RV radial shortening (REF) (with mean of 23.0 ± 4.5 versus 19.3 ± 4.2%), with other RV motion components remaining unchanged. The post-competition decrease in REF was more evident in runners with larger total volume of trainings (R2 = 0.4776, p=0.0002) and higher concentrations of high-sensitivity cardiac troponin I (r = 0.43, p < 0.05) during the preparation period. The decrease in REF was more prominent in marathoners training more than 47 kilometers per week. At stage II, marathoners with a more marked decrease in RVEF and REF had higher galectine-3 levels (r = -0.48 and r = -0.39, respectively; p < 0.05). Running a marathon significantly altered the RV performance of amateur athletes. Transient impairment in RV systolic function resulted from decreased radial shortening, which appeared in those who trained more extensively. Observed ECHO changes correlated with concentrations of the profibrotic marker galectine-3.